Centrum Antyterrorystyczne WNP i Regionalna Struktura Antyterrorystyczna SOW jako elementy systemu zwalczania terroryzmu .......... 141 - Kraj, Kazimierz (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
The article discusses the functioning of the CIS Anti-Terrorist Center and the SCO Regional Anti-Terrorist Structure. The success of these organizations was the launching of activities creating systems of combating terrorism in the sphere of inter-state cooperation and internal structures. Twenty years of work of the ATC CIS and sixteen years of RAS activity are beneficial to all their members. Another significant effect of the functioning of both institutions is the formalization of cooperation, information exchange, unification of law, definition of terrorism and extremism, unification of procedures, joint exercises and establishing communication channels with the authorities of the Member States competent in combating terrorism. These institutions are an example for undertaking inter-state cooperation in the fight against terrorism at the regional level.